Etiological and Clinical Profile of Acute Hepatitis in Children: Experience of A Tertiary Care Hospital in Bangladesh (Dhaka Shishu (Children) Hospital Journal, 2026)
Background: Acute hepatitis is a major public health concern, affecting millions of children worldwide . The four most frequent viruses that cause infection are hepatitis A, B, C, and E. The etiology of acute viral hepatitis varies depending upon several epidemiological and individual factors. Objective: The study aimed to determine the etiology and clinical characteristics of acute hepatitis in pediatric patients in a tertiary care hospital. Methods: This cross-sectional study was conducted in the Department of Pediatric Gastroenterology, Hepatology, and Nutrition, Bangladesh Shishu Hospital & Institute (BSH&I) from January 2023 to January 2024. A total of 50 children aged 1 to 12 years, presenting with acute hepatitis of various etiologies, were included. Acute hepatitis was diagnosed based on clinical manifestation (jaundice lasting